Improving online learning activity interoperability with Acos server. (2nd March 2017) - Sirkiä, Teemu; Haaranen, Lassi
Summary: Modern online learning management systems (LMSs) support a variety of online learning activities, such as animations, exercises, and other interactive learning materials. However, there are many technical challenges in using the same activities in multiple LMSs because content is typically tightly coupled with one protocol to communicate with the LMS and different LMSs use different protocols for launching activities and receiving grades. This leads to low reusability of learning activities and similar content being developed in multiple places. To overcome these issues, we present Acos, a smart learning content server, which emphasizes the reusability of online learning activities by decoupling the content and existing interoperability protocols. It allows integrating the same learning activities into multiple LMSs using different protocols by providing a uniform interface for learning activities. Adapting this architecture allows instructors to choose activities based on pedagogical goals instead of letting technical restrictions of LMSs dictate the content selection process. Copyright © 2017 John Wiley & Sons, Ltd.